Pengaruh Iklan dan Harga Terhadap Kepuasan Pembelian Sepeda Motor Honda Matic Serta Implikasinya Terhadap Loyalitas Konsumen - Ajrina Ramadhani; Yolanda Yolanda; Agus Sudradjat (Fakultas Ekonomi Universitas Borobudur, 2021)
AbstractThe data used in this study are primary data collected from the results of respondents'answers based on the questionnaire given, as many as 98 people. The data processing methoduses the Path Analysis method with the help of SPSS version 21.0. The statistical test used apartial significance test (T test) and a simultaneous significant test (F test).The results show that advertising has a direct effect on purchasing decisions, price has adirect effect on purchasing decisions, advertising has a direct effect on consumer loyalty, pricehas a direct effect on consumer loyalty, purchase decisions have a direct effect on consumerloyalty, advertising has an indirect effect. on consumer loyalty through purchasing decisions andprices indirectly affect consumer loyalty through purchasing decisions.Keywords: Advertising, Price, Purchase Decision, Consumer Loyalty